Evaluation of Hydraulic Performance of Drip Irrigation System - Kumar, Sandeep; Singh, Pratap (Journal of Agricultural Engineering, 2007)
The study was conducted to evaluate the hydraulic performance of drip irrigation system with four emission devices viz dripper, micro-tube, drip-in and drip tape. The different hydraulic measures viz uniformity coefficient. emission uniformity, coefficient of variation and coefficient of manufacturing variation at different spacing and at different operating pressure head were determined by measuring discharge of different emission devices. At a particular spacing, the uniformity coefficient and emission uniformity increased while coefficient of variation decreased as the operating pressure head increased for all emission devices. The coefficient of manufacturing variation was lowest for micro-tubes and highest for drip tape. The suitability/unsuitability of different emission devices was discussed. The micro-tube was not suitable for close spacing. A computer software for hydraulic performance evaluation of drip irrigation system was also developed.